2011
DOI: 10.1200/jco.2010.31.7883
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Oral Tongue Squamous Cell Carcinoma in Young White Women, Age 18 to 44 Years

Abstract: OTSCC is increasing among young white individuals age 18 to 44 years, particularly among white women. Young white women may be a new, emerging head and neck cancer patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
397
7
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(446 citation statements)
references
References 27 publications
27
397
7
15
Order By: Relevance
“…Most diagnosed patients in this study were between 51 and 70 years old (53.9%), which is in accordance with the literature (3,9,16,19) indicating that age is probably a risk marker for OSCC (16). However, Patel et al (6) showed an increased incidence among white female young individuals, aged 18 to 44 years, postulating that there may be a new and emerging head and neck cancer population.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Most diagnosed patients in this study were between 51 and 70 years old (53.9%), which is in accordance with the literature (3,9,16,19) indicating that age is probably a risk marker for OSCC (16). However, Patel et al (6) showed an increased incidence among white female young individuals, aged 18 to 44 years, postulating that there may be a new and emerging head and neck cancer population.…”
Section: Discussionsupporting
confidence: 80%
“…However, in recent decades, there has been an increasing trend of OSCC development in females and young adults, for whom other etiological factors like genetic heritage, dietary habits and Human Papilomavirus (HPV) infection have been pointed out as causes (5)(6)(7). It has been observed that environmental and cultural differences may be closely related to the average occurrence of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, rates of cancers of the oral tongue, base of tongue, and palatine tonsils have continued to rise by 2-4% among younger men. 2,3 This may, in part, be explained by the increased prevalence of a subset of oropharyngeal carcinoma associated with human papillomavirus (HPV), mostly HPV-16. [4][5][6][7] Importantly, p16 overexpression is noted in almost all HPV-associated head and neck cancers and indicates that the virus is transcriptionally active.…”
mentioning
confidence: 99%
“…Several studies have shown a high rate of occult nodal metastasis (20-40%) in tongue SCC patients with no evidence of regional spread on clinical or radiographic evaluation (8,(10)(11)(12)(13)(14)(15). There is a tendency that tongue cancer increases in young females in recent 2-3 decades (16)(17)(18). Thus, metastasis suppression is a main and urgent subject in the treatments of patients with tongue SCC.…”
Section: Introductionmentioning
confidence: 99%